On asymptotic local laws for arithmetic functions - Kubilius, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Кубилюс. Об асимпотических локальных законах распределения арифметических функций J. Kubilius. Aritmetinių funkcijų asimptotiniai lokaliniai dėsniai